Hybrid active suspension system of a helicopter main gearbox. (March 2018) - Rodriguez, Jonathan; Cranga, Paul; Chesne, Simon; Gaudiller, Luc
This paper considers experiments on the control of a helicopter gearbox hybrid electromagnetic suspension. As the new generation of helicopters includes variable engine revolutions per minute (RPMs) during flight, it becomes relevant to add active control to their suspension systems. Most active system performance derives directly from the controller construction, its optimization to the system controlled, and the disturbances expected. An investigation on a feedback and feedforward filtered-x least mean square (FXLMS) control applied to an active DAVI suspension has been made to optimize it in terms of narrow-band disturbance rejection. In this paper, we demonstrate the efficiency of a new hybrid active suspension by combining the advantages of two different approaches in vibration control: resonant absorbers and active suspensions. Here, a hybrid active suspension based on the passive vibration filter called DAVI is developed. The objective of this paper is to prove the relevancy of coupling a resonant vibration absorber with a control actuator in order to create an active suspension with larger bandwidth efficiency and low energy consumption. The simulations and experimentation achieved during this suspension system development support this hypothesis and illustrate the efficiency and low energy cost of this smart combination.